Comparação das medidas instrumentais não invasivas e parâmetros clínicos entre o envelhecimento intrínseco e o fotoenvelhecimento da pele dos antebraços - Carvalho, Paula Roberta Silva de [UNIFESP] (2017)
Background: The intrinsic and extrinsic skin aging present biomechanical and morphological differences, which are reflected in the appearance of roughness, superficial and deep wrinkles, atrophy, reduced elasticity, hypo- and hyperpigmentation and actinic keratosis. The photodamage causes accentuation of all these features and increases the risk for development of premalignant lesions (actinic keratosis) and malignant (basal and squamous cell carcinomas). Objective: to evaluate and compare the characteristics of the flexor (with a predominance of intrinsic aging) and extensor (chronically exposed to sunlight area and other environmental factors, with a predominance of extrinsic aging or photoaging) skin surfaces of the forearms. Methods: The cross-sectional study of diagnostic interventions, including 23 females, aged over 60 years. The extensor and flexor faces of right and left forearms were compared in relation to clinical parameters and non-invasive instrumental measures, such as: skin surface (profilometry), viscoelastic properties, hydration (corneometry) as well as dermal thickness and echogenicity (ultrasound). Results: The water content in the corneal layer showed a significant difference as the flexor area showed an average value greater than the extensor face. The average of the measurements obtained by high-frequency ultrasound showed difference between the faces. The skin surface measurements showed significant differences when compared roughness and desquamation of the extensor and flexor faces on both forearms, but for the flexor face, the differences were smaller. Regarding the wrinkles depth, there was a significant difference of average between the evaluated faces only for the left forearm (p = 0.017), once the flexor face presented an average value greater than the extensor. There was no significant correlation between measurements of the aqueous content of the corneal layer and the viscoelastic properties of the skin, as well as among those obtained by ultrasound. In the prophylometry, only the scaling presented a negative correlation with the corneometry. The visco-elastic properties of the skin showed a positive correlation between the faces. The measurements obtained by the ultrasound and the visco-elastic properties of the skin showed a positive correlation in the flexor face. In the extensor face, there was a positive correlation between roughness, scaliness and wrinkle depth. In the flexor face, the depth of the wrinkles presented negative correlation with a dermal thickness. Dermal density showed negative correlation with other ultrasound measurements. These results were in agreement with established clinical parameters such as wrinkles, elastosis, decreased elasticity and water content, demonstrating the differences between photoaging and chronological aging. Conclusion: Significant differences in the biophysical characteristics of the extensor and flexor surfaces of the forearms were detected. The non-invasive instrumental measures were positively correlated with clinical findings. We concluded that they are useful tools for the evaluation of photoaging and chronological aging in clinical research, as efficacy and safety parameters.